A representação da figura do diabo no tríptico Juízo Final (1482) de Hieronymus Bosch - Oliveira, Grasiela Prado Duarte De [UNIFESP] (2019)
The present work will deal with the analysis of the diabolical being in the work of art of the painter Hieronymus Bosch (1450 - 1516), having as its object the Last Judgement triptych (1500 - 1505), displayed in the Akademie der Bildende Künste, Vienna. Bosch did not seek to stand out for the same aspects and techniques as other Flemish painters of his time. His religious paintings, like the Last Judgment, sought to warn, moralize the observer, and his sources allowed the transfer of beasts and monsters from manuscripts illuminations to the wide support of the altarpieces. Hybridizations of beasts, recurring in medieval and late medieval manuscripts marginalia, worked as a prism for the creation of demons as varied as they were in the Viena Last Judgment, and other similar works. Thus, Bosch composes the three parts the triptych, in order to fill the panels with demons. The left panel, Paradise, is not a place of rejoyce after judgment, but it is a view of the past, where angels and human fall, as we can see in the fall of the rebel angels, the creation of Eve, temptation and expulsion of Adam and Eve. Satan is present in Paradise, deceiving the first couple on earth. The central panel, Last Judgement, shows us a hostage environment of damnation and a profuse diversity of demons. Hell, in continuation of the disgrace of the central panel, keeps the punishments and sentences on the sinners to remind them why they are there, alluding to their own sins in the proceedings.